Combining and crafting institutional tools for groundwater governance - Bruns, Bryan Randolph; Meinzen-Dick, Ruth S. (International Food Policy Research Institute, 2022)
How could having farmers play experiential games contribute to improving groundwater governance? These games are an example of an innovative procedure, a policy instrument or institutional tool, which those involved in improving groundwater governance could use to understand their problems and opportunities; consider and possibly agree on norms or rules that might avoid aquifer depletion, and create shared gains that use water more productively. Institutional tools for groundwater governance could help deal with complex nexus linkages and achieve gains such as transitions to solar-powered pumping, aquifer recharge and storage to buffer against drought, and protecting and regenerating ecosystems. The concept of a groundwater governance toolbox offers a metaphor for thinking about the variety of policy instruments available and how they might be chosen, combined, and adapted to create customized toolkits to solve problems and achieve gains in specific contexts. New policies are typically layered on top of existing sets of institutions that govern relationships between people and water. This makes it crucial to understand existing knowledge and institutions and how those may interact with institutional changes. The thesis of the paper is that institutional tools need to be combined and crafted to fit contexts, including political economy constraints, opportunities, and solutions.